Guideline-directed medical therapy optimization among multi-ethnic groups of heart failure with reduced ejection fraction patients - C Chelfi Zhi, Fei Chua; B. K., Chung; Hwei Sung, Ling; K. C., Cheah; S.L., Kwa; J., Namasoo; C. H., ChaI; P. W., Ting; M. J., Khaw; J. K. W., Wong; A. Z. Y, Koh; W. K., Ho; et al. (European Society of Cardiology, 2025)
Background: Despite established guidelines, there is still substantial gap in guideline-directed medical therapy (GDMT) prescription among heart failure with reduced ejection fraction (HFrEF) population. The implementation of heart failure (HF) clinic could be a strategy to improve GDMT optimization. Objective: This study investigated the usage of GDMT and clinical outcomes of HFrEF patients in HF clinic. Methods: This is a retrospective, observational study that reported HFrEF patients followed up at HF clinic in ten hospitals, inclusive of one cardiology centre and nine hospitals without cardiology service, from January 2021 until June 2023. GDMT utilization at 6-month post HF clinic recruitment was analyzed. Results: A total of 416 patients (78.1% male, mean age 55.6 (13.5 years) were reported. Majority of the population was local indigenous population (46.1%), followed by Malay (29.5%) and Chinese (23.8%). At baseline, there were 65.9% patients on renin-angiotensin-aldosterone system (RAAS) blockers, 76.2% on beta blockers, 62.7% on mineralocorticoid receptor antagonists (MRAs), and 18.3% on sodium-glucose cotransporter-2 (SGLT2) inhibitors. Patients on three or four GDMT pillars were 41.3% and 10.9% respectively. At 6-month, GDMT prescriptions increased across all pillars, 89.2% RAAS blockers, 93.0% beta blockers, 86.3% MRAs and 57.0% SGLT2 inhibitors. The number of patients treated with at least three GDMT pillars also increased, with 37.6% on three and 45.6% on four pillars. The mean ejection fraction had been shown to improve from 27.7% (7.86%) at baseline to 38.4% (13.5%) at 6-month. The 6-month all-cause mortality and HF emergency visit or hospitalization were 8.5% and 7.2% respectively. Conclusion: This study concluded that HF Clinic improved GDMT prescriptions, which was associated with improvement in ejection fraction among HFrEF patients.